The Influence of Organizational Change and Company Regulations on Employee Satisfaction - Putri, Yuliana; Oktaviani, Oktaviani (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
Organizational change and company regulations are important factors affecting employee satisfaction in dynamic work environments. This study aims to analyze the influence of organizational change and company regulations on employee satisfaction in the Stockfitting department of PT Glostar Indonesia 1 Cikembar Sukabumi. The research method employed a quantitative approach with survey design. Primary data were collected through questionnaires distributed to 48 employees selected using simple random sampling technique from a population of 93 employees. The research instrument consisted of 24 statement items measuring organizational change (8 items), company regulations (6 items), and employee satisfaction (10 items) using a Likert scale. Data analysis was conducted using multiple regression analysis with SPSS version 26, preceded by validity, reliability, and normality tests. The results showed that organizational change and company regulations simultaneously have a significant effect on employee satisfaction with an F-calculated value of 36.564 and significance of 0.000. The R Square value of 0.619 indicates that 61.9% of employee satisfaction variability can be explained by these two independent variables. Partially, organizational change significantly affects employee satisfaction (sig. 0.001) and company regulations also have a significant effect (sig. 0.000). The company is recommended to optimize the implementation of responsive organizational changes and apply fair and transparent company regulations to enhance employee satisfaction.